Musica Antiqua: Lebendige Alte Musik, 1966-2005 - Clemencic, René 1928-2022 (Hohenems Bucher, 2007)
Presentation and commentary on the 152 concerts of the MUSICA ANTIQUA cycle, conceived and conducted by René Clemencic between 1966 and 2005 in the Brahms Hall of the Vienna Musikverein. An exciting, richly illustrated history of historical musical performance practice from the Middle Ages, the Renaissance and the Baroque.
René Clemencic (1928-2022) was an Austrian composer, harpsichordist, musicologist and conductor. He was one of the pioneers in the rediscovery of early music and authentic performance practice.
152 Konzerte
Keywords: Gesellschaft der Musikfreunde (Vienna, Austria); 20th Century (1901-2000); 21st Century (2001-2100); Early music; Concert; Vienna (Austria)